PENGEMBANGAN PEMANFAATAN SUMBERDAYA KEPULAUAN PULAU TANAKEKE KABUPATEN TAKALAR PROVINSI SULAWESI SELATAN - Mutmainnah Mutmainnah (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2014)
Tanakeke Island have the potential of natural resources. The potential is there agriculture, fishing, and tourism, wich require proper utilization so that existing activities meet the fulfiil of carrying capacity. This research was conducted in Tanakeke Island in October 2005, by surveying and interviewing techniques. The data were analyzed by using Multi Criteria Decision Making (MCDM). In MCDM, weighted values that most influence on the selection criteria, based on factors that include factors bioteknis assessment, consisting of water quality (brightness, current, substrate, pH, salinity and temperature), land area, the availability of fresh water, biological diversity, technology, resource availability and suitability of land; environmental factors which include linkages mangrove ecosystems, coral reefs, seagrass and excessive exploration; Economic factors include market and financial analysis; socio-cultural factors include motivation, work experience, number of indigenous labor / hereditary habits and institutional factors include farmers, capital institutions, regulations, and informal leadership to determine the priority aspects of resource use will be developed. The analysis showed that seaweed farming activities have the highest scoring at level 1 with a value of 2.65 compared to other activities that include fishing, aquaculture, tourism, conservation and residential